Effectiveness and Safety of DLBS3233 in Newly Diagnosed Type 2 Diabetes Mellitus: A 12-week Clinical Trial - Heri Nugroho; Nurmilawati Nurmilawati; Diana Novitasari; Lidia Rombeallo; Rambu Farah Effendi; Reski Reski; Intan Surayya; Nugroho Agung Daryanto; Solomon Putera; Raymond Rubianto Tjandrawinata (Acta Medica Indonesiana)
Background: DLBS3233, recognized as an agent enhancing insulin sensitivity, has exhibited promise as a therapeutic option for addressing type 2 diabetes mellitus (T2DM). This study aimed to evaluate the effectiveness and safety of DLBS3233, a natural compound, in individuals newly diagnosed with T2DM. Methods: A 12-week double-blind, randomized, placebo-controlled clinical trial was conducted with 104 eligible participants. They were assigned to receive DLBS3233 or a placebo along with lifestyle modifications. Various metabolic parameters, including fasting and post-meal plasma glucose levels at two hours, fasting insulin level, HOMA-IR, adiponectin level, lipid profile, superoxide dismutase (SOD) activity, GLUT-4 concentrations, and body weight measurements, were assessed at baseline, Week 6, and Week 12. Safety parameters assessment will include vital signs, liver function, renal function and adverse event. Results: Participants exhibited similar demographic characteristics in both groups. While no significant changes were noted in fasting plasma glucose and most other parameters, the DLBS3233 group significantly reduced 2-hour postprandial glucose at Week 12 (p = 0.026). There were no substantial differences in A1c levels, fasting insulin, insulin resistance, adiponectin levels, or lipid profiles between the two groups at any point in time. Safety parameters, including blood pressure, liver enzymes, heart rate, gamma GT, and serum creatinine, remained comparable between the groups. Conclusion: DLBS3233 showed potential for improving postprandial glucose control in newly diagnosed T2DM individuals. Although significant changes were limited, the study suggests that DLBS3233 could enhance glycemic regulation. The safety evaluation indicated no adverse effects on vital parameters. Further research with larger samples and more prolonged duration is warranted to comprehensively explore DLBS3233’s potential in T2DM management.